An e-Health Decision Support System for Improving Compliance of Health Workers to the Maternity Care Protocols in South Africa - Horner, V.; Rautenbach, P.; Mbananga, N.; Mashamba, T.; Kwinda, H. (Applied Clinical Informatics, 2013)
Background: There are problems of quality in maternity services at primary health care level in South Africa. Many of these problems can be traced to non-adherence to the maternity care guidelines and lack of tools to support clinic staff and managers in their roles. Objective: The aim of this research was to investigate the utility of e-health (computerized) decision support systems at addressing the problem of compliance of health workers to the maternity care guidelines at primary health care in South Africa. At present there are no documented studies on e-health clinical decision support systems for primary health care in South Africa, though clinical decision support systems for primary health care are listed as part of the e-health strategy of the National Department of Health. Methods: An e-health decision support system named the Bacis (Basic Antenatal Care In-formation System) Program was developed, then implemented and evaluated at a primary health care clinic. The duration of the study was two years: this includes development, implementation and evaluation.Results and Conclusion: There was an overall improvement in compliance from 85.1 % to 89.3%. This result was not statistically significant. However when results were stratified into specific categories, the Bacis Program showed statistically significant improvement in compliance over the checklist system in three out of nine important categories. These are compliance at booking, patients younger than 18 years and patients booking after week 20. Further, insights and experience were also gained on development and implementation of clinical information systems at resource strained environments such as primary health care in South Africa. These results, insights and experience are invaluable for the implementation of the proposed e-health strategy in South Africa.Citation: Horner V, Rautenbach P, Mbanang N, Mashamba T, Kwinda H. An e-health decision support system for improving compliance of health workers to the maternity care protocols in South Africa. Appl Clin Inf 2013; 4: 25–36http://dx.doi.org/10.4338/ACI-2012-10-RA-0044
Keywords: Clinical decision support systems; maternal health care; guideline adherence; primary health care